Vehicles for scaling out mitigation options in rice production in Vietnam: Cooperative and contract farming systems for water management - Tran, Dai Nghia; Le, Huy Huan (2019)
Greenhouse gas emissions from rice production have been identified as a key mitigation focus for Vietnam to meet its Nationally Determined Contributions committed to the Paris Agreement. Shifting to a production landscape that adopts Alternate Wetting and Drying (AWD), which refer to the practice wherein fields are intermittently drained and allowed to dry before being flooded again, can reduce emissions from rice production by 50%. This practice was selected by stakeholders as a priority for scaling out. The study presented here analyzed the process of government coordination and the roles of farmer cooperative groups and private industry pertaining to contract farming as a vehicle for out-scaling AWD. Government officials at the national and provincial level, as well as representatives from private industry and farmer cooperatives, were interviewed to identify enabling factors and limitations to coordination. To further assess the scaling potential of AWD, this study determined the barriers to scaling out as perceived by different actors in the rice value chain and provided recommendations as ways forward. The end goal of this study was to collaborate with the government of Vietnam to combine its findings with data collected from parallel studies in co-designing an implementation framework. The framework, in turn, would guide Vietnam’s rice-related mitigation strategy to meet the 2030 emission reductions that the country pledged to the Paris Agreement.